2019
DOI: 10.1088/2040-8986/ab2a51
|View full text |Cite
|
Sign up to set email alerts
|

High-power all-fiber wavelength-widely-tunable Tm3+-doped fiber laser Q-switched by TI-SA

Abstract: A wavelength widely tunable all-fiber Tm3+-doped double clad fiber laser by using topological insulator (TI) as saturable absorber (SA), for the generation of large energy passively Q-switched pulse, is demonstrated. This 2 μm fiber laser source can generate an average output power as high as 195 mW, corresponding to a pulse energy of ∼3 μJ, and the laser wavelength can be widely tuned from 1935.42 to 2048.85 nm. This high-performance Q-switched operation is implemented by purpose laser cavity optimization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In 2019, Zhang et al reported a TDF laser using the Bi 2 Se 3 as the SA. Its wavelength could be tuned from 1935.42 to 2048.85 nm with a tunable filter [89].…”
Section: 5 μM Lasersmentioning
confidence: 99%
“…In 2019, Zhang et al reported a TDF laser using the Bi 2 Se 3 as the SA. Its wavelength could be tuned from 1935.42 to 2048.85 nm with a tunable filter [89].…”
Section: 5 μM Lasersmentioning
confidence: 99%